The usefulness of edible and medicinal Fabaceae in argentine and Chilean Patagonia: Environmental availability and other sources of supply - Molares, Soledad (2012)
Fabaceae is of great ethnobotanical importance in indigenous and urban communities throughout the world. This work presents a revision of the use of Fabaceae as a food and/or medicinal resource in Argentine-Chilean Patagonia. It is based on a bibliographical analysis of 27 ethnobotanical sources and catalogues of regional flora. Approximately 234 wild species grow in Patagonia, mainly (60) in arid environments, whilst the remainder belong to Sub-Antarctic forest. It was found that 12.8 (30 species), mainly woody, conspicuous plants, are collected for food or medicines. Most of the species used grow in arid environments. Cultivation and purchase/barter enrich the Fabaceae offer, bringing it up to a total of 63 species. The richness of native and exotic species, and the existence of multiple strategies for obtaining these plants, indicates hybridization of knowledge and practices. Only 22 of the total species used are mentioned in bothcontexts of food and medicine, reflecting low-use complementation. This study suggests a significant ecological appearance and a high level of availability in shops and exchange networks in Patagonia, highlighting the need to consider the full set of environmental and socioeconomic factors in research related to the use and cultural importance of plants in regional contexts.